LEARNER-CONTENT INTERACTION IN AN ONLINE ENGLISH LEARNING COURSE AT A VIETNAMESE UNIVERSITY - Thach, Pham Ngoc (VNU Journal of Foreign Studies; Vol 34 No 5, 2018)
Interaction plays a critical role in both traditional and online learning processes. For online learners of English, interaction with the course content is especially vital because it provides them with necessary knowledge in language competence and contributes to the success of online learning. This paper presents the findings of a study about learner-content interaction in an online English language learning course implemented at a university in Vietnam. The study findings reveal that the learners were confident in using the online course, but they did not particularly appreciate its usefulness. The study suggests that in the context where online language learning is at infancy like Vietnam, providing continuous technical support is crucial to promote autonomous learning.